The Effect Of The Implementation Of The Regional Financial Management Information System (Sipkd), The Government's Internal Control System (Spip) And The Role Of Internal Auditors On The Quality Of The Finansial Statements Of The Binjai City Goverment - Wintari Harahap; Erlina; Keulana Erwin (Institute of Computer Science (IOCS), 2022)
The objective of this study was to analyze and determine the effect of the implementation of the Regional Financial Management Information System (SIPKD), the Government’s Internal Control System and the Role of Internal Auditors on the Quality of Financial Statements of the Binjai City Government. The type of research used is causal research. The population in this study was SKPD employees of the Binjai City district Goverment which amounted to 124 employees from 42 SKPD. The research data was obtained from questionnaire (primary). The data analysis method used is structural equation modeling-partial least square (SEM-PLS) using SmartPLS software. The results of this study show that the Regional Financial Management Information System (SIPKD), the Government’s Internal Control System (SPIP) and the Role of Government Internal Auditors each have a significant positive effect on the Quality of The Financial Statements of the Binjai City Government. This means that if the Financial Management Information System, internal control system and the role of internal auditors are improved, it will improve the quality of financial statements.